Gaming as an English Language Learning Resource among Young Children in Denmark. (20th July 2016) - Jensen, Signe
Abstract : This paper presents a study of Danish young English language learners' (YELLs') contact with and use of Extramural English (EE) (N = 107, aged 8 (n = 49) and 10 (n = 58)). They have received little formal English instruction: two weekly lessons for one year. Data on EE-habits were collected with a one-week language diary (self-report with parental guidance). Participants reported minutes spent each day on seven EE-activities: gaming, listening to music, reading, talking, watching television, writing and other. Vocabulary proficiency scores were obtained using the Peabody Picture Vocabulary Test (PPVT™-4). The results show that most time was spent on gaming, music and watching television. Boys gamed significantly more (p < .001) than girls (235 minutes/week vs. 47 minutes/week). Additionally, the results show that gaming with both oral and written English input and gaming with only written English input are significantly related to vocabulary scores, in particular for boys. By investigating the EE-habits of YELLs and relations with second language (L2) English vocabulary learning, this study adds valuable new insights and knowledge about a topic that is becoming increasingly important for children in a globalized world.